2020
DOI: 10.1093/fampra/cmaa050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a primary care-based Medical Weight Loss Program on weight loss and anthropomorphic metrics

Abstract: Background Diet and lifestyle intervention programs have been shown to be effective in decreasing obesity/overweight and many associated comorbidities in specialty research settings. There is very little information however as to the efficacy of such programs conducted in usual/typical primary care practices. We analysed effectiveness of the Medical Weight Loss Program (MWLP) designed to specifically address overweight/obesity in the setting of an urban academic primary care practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is therefore essential to create awareness on health behaviours and engage people with ID in lifestyle alterations to decrease body weight. 33 , 40 When interventions are combined with (structural) proactive risk assessments, diseases can be diagnosed at earlier stage . 31 …”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to create awareness on health behaviours and engage people with ID in lifestyle alterations to decrease body weight. 33 , 40 When interventions are combined with (structural) proactive risk assessments, diseases can be diagnosed at earlier stage . 31 …”
Section: Discussionmentioning
confidence: 99%
“… 36 While such interventions can support modest weight loss, they generally lack preference sensitivity and may be difficult to sustain due to use of study-specific personnel and other resources not available in most practice settings. Limited prior work has observed the outcomes of weight-focused visits with primary care–based ABOM diplomates 21 , 37 and with nondiplomate PCPs assisted by EHR-based tools to support obesity treatment decision-making. 38 …”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent systematic review and metaanalysis of randomized clinical trials of weight management interventions in primary care settings reported predominant use of lifestyle counseling interventions 36. While such interventions can support modest weight loss, they generally lack preference sensitivity and may be difficult to sustain due to use of study-specific personnel and other resources not available in most practice settings.Limited prior work has observed the outcomes of weight-focused visits with primary care-based ABOM diplomates21,37 and with nondiplomate PCPs assisted by EHR-based tools to support obesity treatment decision-making 38.…”
mentioning
confidence: 99%